Dynamic nuclear magnetic resonance field sensing with part-per-trillion resolution - Simon Gross (Nature Portfolio, 2016)
The measurement of high magnetic fields has been limited to sensitivities in the nanotesla range. Here, the authors report advances in high-field magnetometry based on nuclear magnetic resonance, achieving resolution in the order of picoteslas or one part per trillion in relative terms.